Gamma Radiography Testing of Collimators for Boron Neutron Capture Therapy - Deo Clinton Maranatha Simangunsong; Yohannes Sardjono; Budi Setyahandana; Sigit Santosa; Fajar Nurjaman (ASEAN Journal on Science and Technology for Development, 2019)
Boron neutron cancer therapy is a cancer treatment method that encompasses epithermal neutron irradiation of boron delivered to tumor cells. Using collimators, fast neutrons are moderated into epithermal neutrons. When radiation is performed, neutron beams are emitted and filtered by a collimator. In this study, 12 collimators used in the BNCT process were inspected for their quality, in terms of defects or flaws. The inspected collimators were manufactured by centrifugal casting and were composed of 99% pure nickel. They had the following dimensions: height of 145 mm, outer diameter of 190 mm, inner diameter of 160 mm, and thickness of 15 mm. The inspection method used was gamma radiography testing with an Iridium-192 gamma source. Using a single wall single image technique, the collimators were exposed for 30 seconds. Six FUJI films were placed behind the object to record the resulting images, which showed light or dark areas on each collimator, the latter of which indicated porosity or flaws. Based on these images, collimators 1 and 5 were found to contain cracks, and porosity was identified in almost all of the collimators. It is suggested that both collimators with cracks be recycled, while the collimators with porosities should be investigated further to determine their suitability for boron neutron cancer therapy.